RELATIONSHIP BETWEEN SOCIAL DESIRABILITY AND ABILITY PERSONALITY VARIABLES WITHIN JOB APPLICANTS - Tarjono, Hermawan (Journal of Human Capital, 2008)
In employment selection test, use of inventory-type personality testis common in many companies in Indonesia. One of the limitations of inventory-type personality tests is the opportunity for job applicants to provide response in socially desirable manner While test users may question the validity of the test results, it may not be appropriate to jump to conclusion that social desirability is a "bad" thing. Using sample of 142 real job applicants, this study investigates the relationship between social desirability with four ability-personality variables, i.e. cognitive intelligence quotient (/Q), adversity quotient (AQ), achievement motivation (nAch), andmental health (MH). The result shows that /Q, AQ, and MH, influence social desirability at 5% level of significance. Keywords: employment, personality, relationship, ability, desirability